2011
DOI: 10.1097/brs.0b013e3181ebd86f
|View full text |Cite
|
Sign up to set email alerts
|

An Arterial Pulse Examination Is Not Sufficient for Diagnosis of Peripheral Arterial Disease in Lumbar Spinal Canal Stenosis

Abstract: The results of the prospective study define the rate of occurrence of combined LSCS and PAD using ABI and TBI tests for the first time, and the findings suggest that screening for PAD should be conducted in LSCS patients. ABI and TBI tests are necessary for PAD screening in outpatients, whereas observation of the arterial pulse in the lower extremities is necessary but not sufficient for PAD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…However, PAD is often misdiagnosed in older patients with LSS because it is difficult to distinguish vascular IC from neurogenic IC. Therefore, spine surgeons often overlook the possibility of PAD in patients with severe LSS 18) . In a previous study, the coincidence of PAD with LSS was similar to the prevalence of PAD in older individuals (6.7%) 27) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PAD is often misdiagnosed in older patients with LSS because it is difficult to distinguish vascular IC from neurogenic IC. Therefore, spine surgeons often overlook the possibility of PAD in patients with severe LSS 18) . In a previous study, the coincidence of PAD with LSS was similar to the prevalence of PAD in older individuals (6.7%) 27) .…”
Section: Discussionmentioning
confidence: 99%
“…To establish a screening test for PAD, ankle-brachial index (ABI) is commonly used. In previous reports, ABI has been found to be highly sensitive and specific for PAD screening 10 , 18 , 20 , 23 , 24) .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Reduced pulses at the foot and leg are a pathologic finding of vascular claudication, but the reliability and validity of pulse palpation are low [21][22][23]. Alternatively, ABI can be useful either as a screening tool for the primary prevention of PAD or as a tool for monitoring the therapeutic efficacy in secondary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in older people, the clinical picture may be blurred by accompanying illnesses. For example, it has been reported that 26% of elderly patients with lumbar spinal stenosis also have peripheral arterial occlusive disease (PAOD) (8), and a comparable percentage suffers from coxarthrosis (9). Meanwhile, a study from the Far East suggests that 100% of over 70-yearold patients with lumbar stenosis have either osteoporosis or osteopenia, although this finding clearly cannot be directly applied to the Central European population without further study (10).…”
Section: Clinical Manifestationsmentioning
confidence: 99%